2017
DOI: 10.1017/cem.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

What to do when a patient wants to record a patient-physician interaction in the emergency department

Abstract: Recent technological advances allow for instantaneous high quality video and audio recordings with the touch of a button. In Canada, patient privacy is highly regulated by provincial legislation, although patients themselves have little in the way of laws or regulations to observe. Patients taking video recordings of their own medical care does not currently fall under any of the provincial privacy laws. With no such governance for the general public, patients generally have greater freedom to record a patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Although patient privacy is highly regulated by provincial legislation, much of the burden for privacy is placed on clinicians, leaving patients with relatively few regulations to follow. 5,7,8 This situation provides patients with greater freedom to record a patient-physician interaction. Current policy on ED video recording within the Saskatchewan Health Authority leaves the decision to record to the physician's discretion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although patient privacy is highly regulated by provincial legislation, much of the burden for privacy is placed on clinicians, leaving patients with relatively few regulations to follow. 5,7,8 This situation provides patients with greater freedom to record a patient-physician interaction. Current policy on ED video recording within the Saskatchewan Health Authority leaves the decision to record to the physician's discretion.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, public policy on video recording in the healthcare setting is governed by provincial legislation and varies across Canada at each hospital or ED. 5,8,9 Although studies have looked at the use of video recording for educational and quality assurance purposes, as well as the value of recording the patient/ clinician interaction in clinical settings, 10,11 in our review of the literature, we found no studies quantifying how often patients are recording videos in the ED. We also found no studies detailing why patients want to record videos, or what the attitudes and practices of staff are concerning this practice.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Clinicians in other specialties have used recordings to improve timely patientphysician interactions, particularly regarding understanding and recalling discharge instructions. 10 ED staff commonly record clinical images and test results (e.g., ECGs, radiographs) and, once de-identified, use them for academic purposes and for use by other treating clinicians, such as consultants, attending ED physicians and residents (with identifying information and transmitted via HIPAA-compliant modes).…”
mentioning
confidence: 99%